Meteorological atlas of the Northern Hemisphere lower stratosphere for January and February 1989 during Airborne Arctic Stratospheric Expedition - Newman, Paul A.; Goddard Space Flight Center.; Airborne Arctic Stratospheric Expedition. (Washington, D.C. : National Aeronautics and Space Administration, Office of Management, Scientific and Technical Information Division, 1989)
Prepared at Goddard Space Flight Center. Includes bibliographical references (p. 7). Mode of access: Internet.